Investigating the Internal and External Factors that Affect Growth Business Intention and Corporate Social Responsibility (CSR) Intention among Small Medium Enterprise in Malaysia - Mohamad Karudin, Khairulazmi (2010)
Perniagaan berkskala kecil dan sederhana merupakan komposisi terbesar dalam persekitaran perniagaan di Malaysia.